2009
DOI: 10.2165/11310830-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide and Sigma Receptors as Novel Therapeutic Targets for the Pharmacotherapy of Depression

Abstract: Among the most prevalent of mental illnesses, depression is increasing in incidence in the Western world. It presents with a wide variety of symptoms that involve both the CNS and the periphery. Multiple pharmacological observations led to the development of the monoamine theory as a biological basis for depression, according to which diminished neurotransmission within the CNS, including that of the dopamine, noradrenaline (norepinephrine) and serotonin systems, is the leading cause of the disorder. Current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 185 publications
(179 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, polymorphisms in and around the GAL gene have been associated with panic disorder and anxiety in female patients (Unschuld et al, 2008(Unschuld et al, , 2010. As a result of its expression in the amygdala (Miller et al, 1993b;Planas et al, 1994a) and its known role in mood modulation (Crawley et al, 2002;Hobson et al, 2006;Karlsson and Holmes, 2006;Madaan and Wilson, 2009;Paschos et al, 2009;Rotzinger et al, 2009), GAL and its three receptors have received a great deal of attention by researchers attempting to understand the role of the galaninergic system in chronic anxiety and depression and to develop novel therapies. Indeed, a recent GWAS analysis demonstrated evidence for an association between polymorphisms close to the GAL gene locus and major depressive disorder (Wray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polymorphisms in and around the GAL gene have been associated with panic disorder and anxiety in female patients (Unschuld et al, 2008(Unschuld et al, , 2010. As a result of its expression in the amygdala (Miller et al, 1993b;Planas et al, 1994a) and its known role in mood modulation (Crawley et al, 2002;Hobson et al, 2006;Karlsson and Holmes, 2006;Madaan and Wilson, 2009;Paschos et al, 2009;Rotzinger et al, 2009), GAL and its three receptors have received a great deal of attention by researchers attempting to understand the role of the galaninergic system in chronic anxiety and depression and to develop novel therapies. Indeed, a recent GWAS analysis demonstrated evidence for an association between polymorphisms close to the GAL gene locus and major depressive disorder (Wray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…46,49,50 Paschos et al reported up-regulated of NE in the peripheral nervous system, and downregulation in the hippocampal region at times of depression. 51 Ferraro et al reported an increase in plasma NE in patients with type 1 diabetes. 52,53 While others have reported a decrease in thalamic NE in diabetic animals subjected to stress.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the complexity of both depression and PET sets limits on the interpretation of findings. Most PET studies of depressive disorders have been based on the monoamine hypothesis (Schildkraut et al 1968;Schildkraut and Kety 1967), despite the clear-cut need for exploring other strategies (Hindmarch 2002;Berton and Nestler 2006;Pittenger and Duman 2008;Paschos et al 2009;Covington, III et al 2010;Wegener and Volke 2010). Here, we first review recent molecular PET reports on depressive disorders in humans.…”
Section: Principles Of Pet Neuroimagingmentioning
confidence: 96%
“…Some of the pathways that may be causally connected to depressive disorders include genes that encode presynaptic vesicular proteins, plasma membrane receptors, intracellular signaling molecules, proteins that regulate the actin cytoskeleton, and the transcriptional regulatory machinery (Covington, III et al 2010). Additional molecular pathways thought to be either causative or curative of depression include neuroplasticity, neuropeptides, and nitric oxide synthase (Pittenger and Duman 2008;Paschos et al 2009;Wegener and Volke 2010). Clearly, responding promptly to ever-changing notions on molecular pathways of depressive disorders constitutes a major challenge for PET neuroimaging.…”
Section: Challenges For Pet Neuroimaging Of Depressive Disordersmentioning
confidence: 99%